Studi Pendekatan Formula Jogja Pada Jaringan Distribusi PT PLN UP3 Pondok Gede - Basri, Hasan; Wiharja, Ujang (UNIVERSITAS PGRI MADIUN, 2022)
PT. PLN (Persero) at the Customer Service Implementing Unit (Unit Pelaksana Pelayanan Pelanggan, UP3) Pondok Gede, in order to make the loss reduction program more effective, first find out whether the biggest contribution to shrinkage in Pondok Gede UP3 is technical or non-technical. By using the shrink formula method, Jogja has several mechanisms to perform the analysis. The results of the Jogja Formula Shrinkage are presented in the Dupont Chart which divides losses into two parts, namely non-technical losses and technical losses, while technical losses are divided into four parts, namely medium voltage network losses, distribution substation losses, low voltage network losses, and house connection losses. So that we can evaluate and analyze these losses and the program's efforts to reduce losses are on target. In the calculation of the cumulative loss of UP3 Pondok Gede globally in the first quarter of 2020, it is 58,403,338 kWh or 12.27%. After performing a calculation simulation using the Jogja Formula, it was obtained with a technical loss composition of a total of 34,813,582 kWh or 7.31% (this technical loss cannot be avoided or eliminated because it is a shrinkage caused by the components of the equipment used), and non-technical losses. engineering of 23,589,757 kWh or 4.95%.